The nucleation of superconductivity in superconducting-ferromagnetic hybrid films - Stamopoulos, D.; Manios, E. (SUPERCONDUCTOR SCIENCE & TECHNOLOGY, 2005)
The nucleation of superconductivity in a hybrid film (HF) that consists of randomly distributed CoPt ferromagnetic nanoparticles (FNs) embedded in a 200 nm Nb layer was studied by combined magnetic and magnetoresistance measurements. The FNs exhibit both soft and hard magnetic behaviour. It is found that both magnetic phases contribute to the modulation of bulk and surface-like superconductivity by broadening their intermediate regime. More specifically, while the soft FNs (SFNs) promote bulk superconductivity, the hard FNs (HFNs) suppress the bulk superconducting state. In contrast, both SFNs and HFNs promote surface-like superconductivity since on the H-T phase diagram the respective boundary line presents abrupt upturns at their corresponding saturation fields. The dependence of the observed effects on the magnetic history gives clear evidence that they are mainly induced by the cooperative action of the FNs. Our experimental results are compared with current theoretical studies on relevant hybrid systems. Finally, the possible applications that such HFs could find in the near future are discussed.